Cold lenses in the Amundsen Sea: impacts of sea ice formation on subsurface pH and carbon - Daisy D. Pickup; Dorothee C. E. Bakker; Karen J. Heywood; Francis Glassup; Emily M. Hammermeister; Sharon E. Stammerjohn; Gareth A. Lee; Socratis Loucaides; Bastien Y. Queste; Benjamin G. M. Webber; Patricia L. Yager (Ocean Science, 2025)
The Amundsen Sea polynya hosts intense sea ice formation, but, due to the presence of relatively warm and salty modified Circumpolar Deep Water, the cold, brine-enriched water is not typically dense enough to sink to the deep ocean. A hydrographic survey of the Dotson Ice Shelf region in the Amundsen Sea using two ocean gliders identified and characterised subsurface lenses containing water with temperatures less than −1.70 °C. These lenses, located at depths between 240 to 500 m, were colder, saltier and denser than the overlying Winter Water (WW) layer. The pH of the lenses was 7.99, lower than WW by 0.02 and the dissolved inorganic carbon concentration was higher in the lenses than WW by approximately 10 µmol kg−1. The lenses were associated with a dissolved oxygen concentration greater than surrounding water at the same depth and density due to the cold temperatures increasing O2 solubility. We hypothesise that these lenses are a product of wintertime surface cooling and brine rejection in areas with intense sea ice formation. They may form in shallow regions, potentially around the Martin Peninsula and Bear Island, where intense upper ocean heat loss occurs, and then spill off into the deeper Dotson-Getz Trough to reach their neutrally-buoyant depth. This is supported by wintertime temperature and salinity observations. This study highlights the importance of shallow parts of shelf seas for generating cold dense water masses in the warm sector of Antarctica. These lenses are widespread in the region of the Dotson-Getz Trough and have the potential to sequester carbon deeper than typical in the region, alongside cooling the water impinging on the Dotson ice shelf base.